Editorial - Verdoolaege, Annelies (Afrika Focus, 2016)
In this current issue we offer you ve top articles from a wide range of different disciplines. Two articles are located in South Africa, one within health sciences and one in theatre studies. Museums in Cameroon, international legal frameworks linking the UK and Mauritius, and the European slave trade in 17th century Madagascar sum up the content of the remaining three articles. As always, we also publish a number of reports, mostly summaries of PhDs on Africa defended at Ghent University. The objective of these reports is to give you an overview of the Africa research taking place at Ghent University. In addition, we also want to give some visibility to these junior researchers, so please have a look at their topics and do not hesitate to get in touch with them for further questions and comments. Enjoy and... have you had a look already at the results of the presidential elections in Somalia?In this current issue we offer you ve top articles from a wide range of different disciplines. Two articles are located in South Africa, one within health sciences and one in theatre studies. Museums in Cameroon, international legal frameworks linking the UK and Mauritius, and the European slave trade in 17th century Madagascar sum up the content of the remaining three articles. As always, we also publish a number of reports, mostly summaries of PhDs on Africa defended at Ghent University. The objective of these reports is to give you an overview of the Africa research taking place at Ghent University. In addition, we also want to give some visibility to these junior researchers, so please have a look at their topics and do not hesitate to get in touch with them.